Detailing the chemical composition of roasted soybeans and the effect for its use in the diet of dairy cows - A. M. Shevchenko; O. V. Zhurenko; D. V. Feshchenko; O. A. Dubova; O. А. Zghozinska (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Roasted soybeans are a complete source of indigestible protein in the rumen, have high sanitary and hygienic indicators, are devoid of non-nutritional substances of ordinary raw soybeans. The SoyPass and RaPass technology provides all the advantages of roasting soybeans and creates prerequisites for prolonged storage of beans for up to two years without prior drying. The introduction of full-fat flattened soybeans roasted by the Roast-A-Matic roaster into the diet of dairy cows leads to an increase in their milk productivity. Certified results of chemical research show that after frying, the percentage of crude protein significantly increased (by 2.92 points, P < 0.05) and the content of total digestible nutrients (by 8.1 %, P < 0.05), urease activity decreased to 0.06 ± 0.007 units of pH. The biological value of soy protein after frying corresponds to the indicators of the reference protein. Two groups of cows were involved in the study: № 1 – high-yielding cows with a daily milk yield of 30.69–35.96 L (n = 307) and № 2 – medium- and low-yielding cows with a yield of 19.05–28.88 L (n = 377). Group № 1 was given 300 g of roasted soybeans (111 g of protein) daily in their diet instead of 250 g of a high-protein supplement (200 g of protein); group No. 2 – gradually replaced 230 g of the supplement (184 g of protein) and 1500 g of 51 % meal (765 g of protein) with 1700 g of roasted soybeans (629 g of protein). In both groups, the 65-day observation period should be divided into 2 periods: 1) a 30-day period of intensive growth with a rapid increase in milk yield (up to +24.2–25.0 %); 2) the period of stabilization (from the 31st to the 65th day), characterized by some fluctuations in the % increase in milk, but in general by reliable maximum values (up to +25.0–36.7 %). The maximum daily volume in group № 1 reached 41.83 ± 1.04 and 41.83 ± 0.3 L (Р < 0.01) on the 32nd and 38th days, respectively. At the same time, the range of the indicators of the individual yield in the group ranged from 10.7 to 11.7 L. Similar indicators for group № 2 were: 32.56 ± 2.74 L (Р < 0.025) on the 58th day and 10.4–23.8 L. So, in the first 30 days of feeding full-fat fried soybeans, there is a rapid but unstable (with fluctuating peaks) increase in milk productivity of cows. During the 2nd month of soy consumption, the maximum milk yield is reached, when the increase in added milk is not rapid, but stable. Thus, it is advisable to introduce 1.5–2.0 kg/day of roasted soybeans (equivalent to 0.3–0.4 kg of fat/day) into the diet of dairy cows.